Bilateral corneoscleritis with retrocorneal plaque as the initial presentation of granulomatosis with polyangiitis - Jia Liu; Bei Zhang (BMC Ophthalmology)
Abstract Background To report a case of bilateral corneoscleritis with retrocorneal plaque lesion as the presenting sign of granulomatous polyangiitis (GPA). Case presentation A 61-year-old female presented with bilateral extensive periphery corneoscleritis with retrocorneal plaque and prominent conjunctival injection. She suffered from progressively blurry vision and pain in both eyes for about 5 years, accompanied by sinusitis. No retinal or orbital abnormalities were noted on examination. A conjunctival and scleral biopsy was performed in the left eye, and the histopathological analysis was consistent with granulomatous inflammation. A full diagnostic workup revealed no obvious abnormal findings except positive cytoplasmic antineutrophil cytoplasmic antibody (cANCA) and proteinase 3-specific antineutrophil cytoplasmic antibody (PR3-ANCA). The patient achieved disease remission with cyclophosphamide and corticosteroid and remained on oral and topical medications with no further loss of vision or discomfort. Conclusions This is a unique documented case of corneoscleritis with retrocorneal plaque lesion as the initial presenting feature of GPA. Our case illustrates that the initial ocular manifestations of GPA involving the cornea and sclera may have atypical lesions. Clinicians should cautiously evaluate the patients to enhance the early diagnosis and promptly initiate treatment measures to prevent vision loss.